Impact of a Nomadic Pastoral Lifestyle on the Gut Microbiome in the Fulani Living in Nigeria - Afolayan, Ayorinde O.; Ayeni, Funmilola A.; Moissl-Eichinger, Christine; Gorkiewicz, Gregor; Halwachs, Bettina; Högenauer, Christoph (Frontiers in Microbiology, 2019)
The co-evolution of the gut microbiota with its human host has revolutionized our current scientific viewpoint about the contribution of diet and lifestyle on human health. Most studies so far have focused on populations living in the US and Europe or compared those with communities from other geographic areas in the world. In order to determine the taxonomic and predicted functional profile of the gut microbiome of a hitherto unstudied human community, we investigated the phylogenetic diversity of the gut microbiota in a community of Fulani nomadic pastoralists, and their semi-urbanized neighbors—the Jarawa. The Jarawa reside in a city (Jos) in the north-central part of Nigeria, and are adapted in part to a westernized lifestyle. The nomadic Fulani lifestyle resembles a mix of Paleolithic and Neolithic lifestyle patterns with a greater predisposition to diseases. The fecal microbiota of the Fulani and the Jarawa were characterized by paired-end Illumina MiSeq sequencing of the 16S rRNA gene, followed by downstream bioinformatics analysis of the sequence reads. The Fulani harbored increased numbers of signatures of microbes that are known to be associated with a foraging lifestyle such as the Bacteroidetes, Spirochaetes, and Prevotellaceae, while the Jarawa were dominated by signatures of Firmicutes, Ruminococcaceae, Lachnospiraceae and Christensenellaceae. Notably, the gut microbiota of the Fulani showed less taxonomic diversity than those of the Jarawa. Although they reside in the same geographical zone, microbial community composition was significantly different between the two groups. Pathogens were predicted to be more abundant in the gut microbiota of the Fulani than of the Jarawa. Predicted pathogenic pathways and pathways associated with the breakdown of fiber-rich diet were enriched in the Fulani, including glutathione metabolism, while pathways associated with the consumption of low-fiber diet and xenobiotics, including fructose and mannose metabolic pathways, and nitrotoluene degradation pathways, respectively, were enriched in the Jarawa. Significant differences in composition between both groups were likely due to differences in diet and lifestyle and exposure to pathogens. These results suggest that microbial diversity may not always be higher in non-industrialized societies than in westernized societies, as previously assumed.